1995
DOI: 10.1017/s0950268800052195
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of epidemic poliovirus from sewage during the 1992–3 type 3 outbreak in the Netherlands

Abstract: To examine the extent of wild poliovirus circulation during the 1992-3 epidemic in the Netherlands caused by poliovirus type 3, 269 samples from sewage pipelines at 120 locations were examined for the presence of poliovirus. The epidemic virus strain was found in 23 samples, all from locations inside the risk area which contained communities that refuse vaccination for religious reasons. By sewage investigation, the wildtype virus was shown to be present in the early phase of the epidemic at two locations, one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 25 publications
1
50
0
Order By: Relevance
“…Researches suggest that Environmental Poliovirus Surveillance (ENV) should be in place during the period between interruption of wild poliovirus (WPV) transmission & certification of eradication and should be continued into the post eradication phase and OPV cessation period to monitor emergence of Vaccine Derived Poliovirus (VDPV) re-emergence of WPV or disappearance of all OPV-related strains [26]. There is also evidence that ENV along with routine AFP case based surveillance is more effective to detect introduction and circulation of Wild Poliovirus (WPV) and Vaccine Derived Poliovirus (VDPV) [27][28][29][30][31]. Environmental surveillance also has a role in new WHO strategy for intensified effort to complete poliomyelitis eradication [32] and can be useful to monitor the efficacy of immunisation initiatives when necessary [26].…”
Section: Resultsmentioning
confidence: 99%
“…Researches suggest that Environmental Poliovirus Surveillance (ENV) should be in place during the period between interruption of wild poliovirus (WPV) transmission & certification of eradication and should be continued into the post eradication phase and OPV cessation period to monitor emergence of Vaccine Derived Poliovirus (VDPV) re-emergence of WPV or disappearance of all OPV-related strains [26]. There is also evidence that ENV along with routine AFP case based surveillance is more effective to detect introduction and circulation of Wild Poliovirus (WPV) and Vaccine Derived Poliovirus (VDPV) [27][28][29][30][31]. Environmental surveillance also has a role in new WHO strategy for intensified effort to complete poliomyelitis eradication [32] and can be useful to monitor the efficacy of immunisation initiatives when necessary [26].…”
Section: Resultsmentioning
confidence: 99%
“…Danes et al (1983) stated that there was a high incidence of enteroviral infections among children aged 5-16 years, but did not provide data for the incidence to be calculated. Some patterns can be seen among cases reported by age (D'Alessio et al, 1981;Miyama et al, 1992;Oostvort et al, 1994), gender (Oostvort et al, 1994;Rodriguez et al, 1997), and proximity to the index case (Hawley et al, 1973;Oostvort et al, 1994;Van der Avoort et al, 1995). Typically, cases were younger children, men, or persons in close contact with index cases.…”
Section: Qualitative Datamentioning
confidence: 99%
“…Polioviruses, coxsackievirus A and B, and echoviruses have been found in rivers (e.g., Payment et al, 1988;Miyama et al, 1992;Tani et al, 1995), but coxsackievirus A and B and echoviruses have also been reported in lakes (D'Alessio et al, 1981) and swimming pools (Kee et al, 1994). Sources of waterborne enteroviruses suggested in the scientific literature include sewage (Oostvort et al, 1994;Van der Avoort et al, 1995), storm sewer discharge and runoff (D'Alessio et al, 1981), human activities (Payment et al, 1988;Kee et al, 1994), and diapers and sullage (Field et al, 1968).…”
Section: Occurrencementioning
confidence: 99%
See 2 more Smart Citations